Can AI Help with Chronic Disease Management? A Deep Dive into Digital Health's Future - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2024)
Can AI Help with Chronic Disease Management? A Deep Dive into Digital Health's Future Chronic diseases—such as diabetes, cardiovascular conditions, and ...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care